Application of standard keratometry values obtained from keratotopographic mapping data to calculate the optical power of a multifocal intraocular lens - Shukhaev, S. V.; Boiko, E. V.; Petrosyan, Yu. M.; Molodkin, A. V. (Rossiĭskiĭ oftalʹmologicheskiĭ zhurnal, 2024)
Purpose of the study is to determine the zones of standard keratometry according to keratotopography data, which will allow for more accurate calculation of multifocal IOL using 10 formulas. Material and methods . The study included 55 patients (55 eyes) who underwent phacoemulsification of cataract or refractive lensectomy with femtolaser accompaniment, implantation of multifocal IOL (Acrysof IQ PanOptix) and achieved the target refraction at different distances. Retrospective calculation of the optical power of the IOL was carried out using biometric data from OA-2000 and keratometric indicators of Pentacam (zones from 0.5 mm to 5 mm in increments of 0.5 mm on the Axial/Sagittal map centered on the apex and pupil) using 10 formulas (SRK/T, Holladay 1, Holladay 2, Haigis, Hoffer Q, Barrett 2 Universal, Olsen, Kane, EVO ver. 2.0, Hill RBF ver. 3.0). For each combination of zone/keratometry value/formula, the average error of postoperative predicted refraction, its difference from zero (Wilcoxon criterion), the median value taking into account the sign, the mean (MAE) and median (MedAE) absolute errors in calculating the spherical equivalent of the IOL, the standard deviation of the mean absolute error (SD) were calculated. Results. All formulas had a shift to myopic refraction, except for the Haigis formula, which shifted towards hyperopia. The absence of a significant difference from zero was shown only by the Kane formula in zones 3.5, 4.5–5.0 mm when centered on the apex and in zones 0.5, 1.5, 2.5–5.5 mm when centered on the pupil. The highest values of MAE were found in Haigis and Olsen formulas, and the minimum values were observed in most formulas in the 4.5–5.0 mm zones. The lowest MedAE values in all ranges were shown by the formulas Kane, EVO, Holladay 1 and Holladay 2. The minimum SD values were found for the formulas Kane, EVO, Holladay 1 and Holladay 2. Conclusion . The Kane formula turned out to be the most accurate in the 4.5–5.0 mm zone. This is followed by the EVO 2 and Holladay 1 formulas in the 4.0 mm zone. The Haigis formula turned out to be the least accurate. The remaining formulas can be recommended for use with SimK Pentacam data in 4.0–5.0 mm zones.